Association between Psychological Flexibility and Health Beliefs in the Uptake of Influenza Vaccination among People with Chronic Respiratory Diseases in Hong Kong - Cheung, Kin Wai (Int J Environ Res Public Health, 2016)
It is common for elderly people and those with such chronic disorders as respiratory diseases to suffer severe complications from influenza, a viral infection. The voluntary uptake of vaccination is vital to the effectiveness of influenza prevention efforts. The Health Belief Model (HBM) is the most commonly used framework in the field of vaccination behavior to explain the decision that people make to accept or refuse vaccination. In addition, psychological flexibility is considered helpful in causing people to be open to adopting new practices that are consistent with their values. This study examined the role of psychological flexibility and health beliefs in predicting the uptake of influenza vaccination among people in Hong Kong. Eligible participants were Hong Kong permanent residents aged 18 years or above with a history of chronic respiratory diseases (CRD). A convenience sample of 255 patients was recruited to participate in a cross-sectional survey in which HBM components and factors of psychological flexibility were assessed. The following variables were found to be significant predictors of vaccination: age, smoking status, comorbidity, previous hospitalization, perceived susceptibility, perceived severity, and psychological flexibility. Enhancing psychological flexibility might be a potential new direction for motivating people to accept influenza vaccination.